Influence of light-induced conical intersection on the photodissociation dynamics of D2+ starting from individual vibrational levels - Halász, Gábor J.; Cederbaum, Lorenz S. (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2014)
Previous works have shown that dressing of diatomic molecules by standing or by running laser waves gives rise to the appearance of so-called light-induced conical intersections (LICIs). Because of the strong nonadiabatic couplings, the existence of such LICIs may significantly change the dynamical properties of a molecular system. In our former paper (J. Phys. Chem. A 2013, 117, 8528), the photodissociation dynamics of the D2+ molecule were studied in the LICI framework starting the initial vibrational nuclear wave packet from the superposition of all the vibrational states initially produced by ionizing D2. The present work complements our previous investigation by letting the initial nuclear wave packets start from different individual vibrational levels of D2+, in particular, above the energy of the LICI. The kinetic energy release spectra, the total dissociation probabilities, and the angular distributions of the photofragments are calculated and discussed. An interesting phenomenon has been found in the spectra of the photofragments. Applying the light-induced adiabatic picture supported by LICI, explanations are given for the unexpected structure of the spectra.
Gesehen am 20.10.2020
Im Titel ist die Zahl 2 tiefgestellt und das Zeichen + hochgestellt